Medical termination of pregnancy in bitches using progesterone receptor blocker - KULASEKAR, K; JOSEPH, CECILIA; RANGASAMY, S (The Indian Journal of Animal Reproduction, 2023)
This trial was undertaken to test the efficacy of progesterone receptor blocker, Mifepristone (Tab.Mifeprin-200 mg, SunPhannaceuticals, Mumbai) in terminating pregnancy in bitches. Ten pregnant bitches brought to the Madras Veterinary CollegeHospital for medical termination of pregnancy were administered Mifepristone at the dose rate of2.5mg/Kg body weight bidorally for 4-5 days. Ultrasonography was done to confirm pregnancy and to monitor fetal viability and resorption after inductionof treatment. In all bitches, pregnancy was terminated between 3-6 with a mean of 4.5 ± 1.5 days after treatment and there was no side effect associated with the treatment. Mifepristone administration is a safe and reliable method to terminate unwanted pregnancy in dogs.
Keywords: Medical termination; pregnancy; progesterone receptor blocker; dogs